Mediatisation of social issues in African public sphere The case of homosexuality in Ivory Coast, Gabon, and Senegal - (:unkn) unknown (My University, 2024)
This paper explores the mediatisation of homosexuality in Sub-Saharan Africa, focusing on Ivory Coast, Gabon, and Senegal. The study investigates how media representations and public discourse contribute to the visibility and politicisation of homosexuality in these countries. Drawing on theories of mediatisation, public sphere, and biopolitics, this research examines the interplay between people working with media, political stakeholders, and social movements in shaping public perceptions and policies regarding homosexuality.
Keywords: African Research